2019
DOI: 10.1111/pce.13524
|View full text |Cite
|
Sign up to set email alerts
|

Ecological significance of light quality in optimizing plant defence

Abstract: Plants balance the allocation of resources between growth and defence to optimize fitness in a competitive environment. Perception of neighbour‐detection cues, such as a low ratio of red to far‐red (R:FR) radiation, activates a suite of shade‐avoidance responses that include stem elongation and upward leaf movement, whilst simultaneously downregulating defence. This downregulation is hypothesized to benefit the plant either by mediating the growth‐defence balance in favour of growth in high plant densities or,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…Particular emphasis is placed on the role of chromatin organization, transcription factors, posttranslational modifications, phytohormones, and metabolites involved in stress management. Plant responses do depend not only on the plant's intrinsic capability to cope with a specific stress but also on habitat conditions and the availability of symbionts, as pointed out by Douma et al () and Mason, Jones, and Felton () in this issue.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Particular emphasis is placed on the role of chromatin organization, transcription factors, posttranslational modifications, phytohormones, and metabolites involved in stress management. Plant responses do depend not only on the plant's intrinsic capability to cope with a specific stress but also on habitat conditions and the availability of symbionts, as pointed out by Douma et al () and Mason, Jones, and Felton () in this issue.…”
Section: Introductionmentioning
confidence: 86%
“…The shade‐avoidance growth response at high plant densities may limit the resources available for defence. Douma et al () tested the relationship between plant density and defence against herbivory by a functional–structural plant model for Brassica nigra . The model shows that optimal plant‐level defence does not monotonically decrease with plant density.…”
Section: Plant Stress Signalling In An Ecological Contextmentioning
confidence: 99%
“…To cope with these environmental changes, sessile plants have evolved integrated mechanisms to respond these complex stress conditions, minimizing damages, while conserving valuable resources for growth and reproduction [ 11 13 ]. As an energy source and a key environmental factor, light influences plant growth, defense, and even ecological structure [ 14 , 15 ]. The perception of light signals by phytochrome photoreceptors initiates downstream signaling pathways and regulates numerous plant processes during growth and defense [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent FSPM studies have indicated that light competition reduces individual plant defence against herbivory ( de Vries et al ., 2018 , 2019 ). In addition, Douma et al (2019) , have shown that it is not only the quantity of light that contributes to plant defence, but also the quality of available light.…”
Section: General Features Of Fspmsmentioning
confidence: 99%